Response letter to the editor regarding, “Impact of WhatsApp on improving denture care knowledge and the awareness of the relationship between edentulism and general health” - Wan Abd. Manan, Wan Nor Hayati; Abg. Abd. Mohd Rizal, Dayang Nur Sharin; Borhan, Farah Wajihah; Lestari, Widya; Ismail, Azlini; Che Musa, Muhd Firdaus; Mohd Ibrahim, Mohamad Shafiq; Yuan, Judy Chia-Chun; Sukotjo, Cortino (Elsevier, 2025)
In the digital age, many healthcare providers have utilized WhatsApp for triage, sending alerts, making referrals, and discussing clinical issues—both in devel- oping and developed countries.2,3 Patients can also be educated through a variety of social media platforms. WhatsApp, has been shown to significantly improve knowledge related to home care for minor illnesses in intervention groups compared with controls.4 Ad- ditionally, another study demonstrated that WhatsApp- based interventions can significantly enhance diabetes education and self-management, with notable im- provements observed at both 6 and 12 weeks compared with control groups.5 A longitudinal study examining the impact of WhatsApp on patient behavior and oral health outcomes is both warranted and planned for the future.